Dermatology Consultation - Çiçek, Demet (Fırat University, 2007)
Objectives: The aim of our study was clinical characteristics of the cases which dermatological consultation were requested and investigations were done during cosultation and evaluation of the conclusions. Material and Methods: A total of 336 patients cosulted a period of five months from different clinics were analysed prospectively. Results: Consultations were requested mostly from internal medicine (118), emergency (37), Chest disease (33), the most common dermatological diseases diagnosed by consultants were infections, eczema, pruritus, urticaria and drug reactions. Local therapy was prescribed in 88% and systemic therapy in 43% of the patients. 9.2% did not receive specific therapy. Conclusion: In the other clinics except dermatology common skin diseases must be established and educational programs associted with these diseases were planned. ©2007, Firat University, Medical Faculty

Giriş: Bu çalışma Dermatoloji konsültasyonu istenen olguların klinik özellikleri, konsültasyon sırasında yapılan incelemeler ve varılan sonuçları değerlendirmek amacıyla yapıldı. Gereç ve Yöntem: Beş aylık sürede farklı kliniklerden konsülte edilen toplam 336 hasta prospektif olarak değerlendirildi. Bulgular: Konsültasyonlar en çok iç hastalıkları (118), acil servis (37) ve göğüs hastalıkları (33) servislerinden istenilmiş olup, konsültanlar tarafından en sık tanı konulan hastalıklar enfeksiyonlar, ekzema, pruritus, ürtiker ve ilaç erüpsiyonlarıydı. Hastaların %88' ine lokal tedavi, %43' üne sistemik tedavi başlanırken %9.2' sine herhangi bir tedavi önerilmedi. Sonuç: Dermatoloji dışındaki kliniklerde sık karşılaşılan deri hastalıkları saptanmalı ve bu hastalıklara yönelik eğitim programları planlanmalıdır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Dermatoloji Konsültasyonlarının Değerlendirilmesi